Digestive wellness : strengthen the immune system and prevent disease through healthy digestion - Lipski, Elizabeth (McGraw-Hill, 2020)
Optimize your overall health through digestive wellness! Fewer antacids and less bloating aren't the only benefits of good digestion. When your digestive system is healthy and balanced, you sleep better, have more energy, think more clearly, experience less pain, and combat disease more effectively. Digestive Health shows how everything from migraines to skin disease to arthritis are connected to your digestive system. And now, this go-to guide has been updated with critical new research and developments. You'll find practical solutions to numerous conditions and disorders, along with expert guidance on the newest advances in testing and diagnosis, nutrition, and natural therapies. A perfect balance of science and practical advice, Digestive Health explains how your digestive system works and what to do when it doesn't function properly. It provides everything you need to take control of your overall health through close, careful attention to your digestive system.